AS-amyloidosis. Dual pathology or novel disease? A multimodality, multi-centre assessment across health and disease. (8th February 2021) - Patel, K; Scully, P; Nitsche, C; Williams, S; Tillin, T; Captur, G; Chako, L; Newton, J; Kennon, S; Menezes, L; Pugliese, F; Fontana, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation onbehalf: AS-Amyloidosis consortium Background: The coexistence of severe aortic stenosis (lone AS) and transthyretin cardiac amyloidosis (lone amyloidosis) is common, but the resultant AS-amyloidosis phenotype is unclear. Purpose: We characterised AS-amyloidosis, hypothesizing that the dual insult of AS-amyloidosis results is a severe phenotype. Methods: We compared four cohorts with deep phenotyping: 81 older age controls, 359 lone AS, 36 AS-amyloidosis (Perugini grade 2 and 3) and 107 lone amyloidosis (Perugini grade 2 and 3). Results: AS-amyloidosis was similar to lone AS with respect to left ventricular mass and LVEF (57 (45, 64)%). It was similar to lone amyloidosis with respect to lateral S" (0.04 (0.03, 0.06) m/s), NT-proBNP (4149 (1449, 6459) ng/L) and troponin T (56 (34, 100) ng/L). Whilst, prevalence of carpal tunnel syndrome (CTS) (17%) and diastolic function (E/A ratio 1.1 (0.8, 2.8)) were intermediate. Conclusion: AS-amyloidosis is not a double insult from AS and amyloidosis, but a mixed phenotype with features similar to lone amyloidosis (cardiac biomarkers), lone AS (remodelling and LVEF) or intermediate (diastology and CTS).